Forbes Greatest Business Stories of All Time - Gross, Daniel (New York J. Wiley & Sons, 1996)
What do Bill Gates, Henry Ford, J. P. Morgan, Mary Kay Ash, and Walt Disney all have in common? Uncompromising vision, a willingness to take risks, and exceptional business acumen. Not only did these individuals amass great fortunes, they revolutionized the business world and helped shape society as we know it. Theirs are just a few of the stories collected in this anthology of commercial ingenuity.
ncludes bibliographical references (p. [352]-357)
Keywords: Success in business-United States -Case studies